Semen collection by urethral catheterization and electro-ejaculation with different voltages, and the effect of holding temperature and cooling rate before cryopreservation on semen quality in the Japanese macaque (Macaca fuscata) - TAKAESU, Noboru; KANNO, Chihiro; SUGIMOTO, Kosuke; NAGANO, Masashi; KANEKO, Akihisa; INDO, Yoriko; IMAI, Hiroo; HIRAI, Hirohisa; OKAMOTO, Munehiro; SASHIKA, Mariko; SHIMOZURU, Michito; KATAGIRI, Seiji; et al. (Journal of Veterinary Medical Science, 2022)
In the Japanese macaque, semen has been collected by electro-ejaculation (EE), using the higher voltage stimuli compared to other species including genus Macaca. Semen coagulates immediately after ejaculation, which makes difficult to produce high-quality semen for artificial insemination. Recently, semen collection using urethral catheterization (UC) has been reported in carnivore and this technique may allow semen collection without coagulation in a less invasive manner. Further, the temporal preservation temperature and cooling rate of semen during cryopreservation affect post thawing sperm quality. In this study, to improve semen quality and quantity, as well as the animal welfare, semen collection was performed by EE with high (5–15 V) or low (3–6 V) voltage, UC and a combination of the two (EE-UC). It has been suggested that a high voltage is necessary for semen collection, but 10 V stimulation was effective enough and 15 V is for additional sperm collection. Also, liquid semen was collected by EE-UC and this could increase the total number of sperm. Further, to improve the post thawing sperm motility, semen was kept at four temperatures (4, 15, 25 and 37°C) for 60 min, and processed with two cooling procedures (slow cooling before second dilution and fast cooling after second dilution). Holding semen at 25°C and fast cooling after the second dilution maintained progressive motile sperm rate. The present results will contribute to the improvement of semen collection and animal welfare of Japanese macaques.